Effect of Sleep Deprivation on the Male Reproductive System in Rats - Choi, Ji Ho; Lee, Seung Hoon; Bae, Jae Hyun; Shim, Ji Sung; Park, Hong Seok; Kim, Young Sik; Shin, Chol (Journal of Korean medical science, 2016)
There has been no study reporting on the influence of sleep deprivation on the male reproductive system including sperm quality. In this study, we hypothesized that sleep deprivation could lead to adverse effect on the male reproductive system. The rats were divided into three groups: 1) control (home-cage, n = 10); 2) SD4 (sleep deprivation for 4 days, n = 10); and 3) SD7 (sleep deprivation for 7 days, n = 10). Sleep deprivation was performed by a modified multiple platform method. Sperm quality (sperm motion parameters and counts), hormone levels (corticosterone and testosterone), and the histopathology of testis were evaluated and compared between the three groups. A statistically significant reduction (P = 0.018) was observed in sperm motility in the SD7 group compared to those of the control group. However, there were no significant differences in other sperm motion parameters, or in sperm counts of the testis and cauda epididymis between three groups. Compared with the control group, the SD4 (P = 0.033) and SD7 (P = 0.002) groups exhibited significant increases of corticosterone levels, but significant decreases of testosterone levels were found in the SD4 (P = 0.001) and SD7 (P < 0.001) groups. Seminiferous tubular atrophy and/or spermatid retention was partially observed in the SD4 and SD7 groups, compared with the normal histopathology of the control group. Sleep deprivation may have an adverse effect on the male reproductive system in rats.